2021
DOI: 10.25115/ecp.v14i28.4177
|View full text |Cite
|
Sign up to set email alerts
|

Basic psychological needs and implicit beliefs of ability in secondary education | Necesidades psicológicas básicas y creencias implícitas de habilidad en educación secundaria

Abstract: El objetivo de este estudio fue analizar la relación entre el desarrollo de las necesidades psicológicas básicas y las creencias implícitas de habilidad en alumnado de Educación Secundaria. La muestra estuvo formada por un total de 97 estudiantes de Educación Secundaria, con edades comprendidas entre los 13 y los 15 años (edad media = 13.32 ± 0.62 años) a los que se les aplicaron los cuestionarios de apoyo a las necesidades psicológicas básicas y creencias implícitas sobre la habilidad en sus clases de Educaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…En este sentido, según la Teoría de la Autodeterminación, la motivación intrínseca y extrínseca afloran cuando la autoeficacia se desarrolla provocando un incremento de la motivación autodeterminada, gracias a la satisfacción de las necesidades psicológicas básicas (NSB) de la autonomía, la competencia y las relaciones personales (Deci & Ryan, 2000;Ryan & Deci, 2017), vinculando los hábitos a la motivación (Hernández-Andreo et al, 2021;Stover et al, 2017). Además, se debe tener en cuenta que la satisfacción de las NSB puede ser predictora positiva tanto de la motivación autónoma, como del autoconcepto físico del alumnado, aumentando la fidelización en la práctica (Valero-Valenzuela et al, 2021).…”
Section: Introductionunclassified
“…En este sentido, según la Teoría de la Autodeterminación, la motivación intrínseca y extrínseca afloran cuando la autoeficacia se desarrolla provocando un incremento de la motivación autodeterminada, gracias a la satisfacción de las necesidades psicológicas básicas (NSB) de la autonomía, la competencia y las relaciones personales (Deci & Ryan, 2000;Ryan & Deci, 2017), vinculando los hábitos a la motivación (Hernández-Andreo et al, 2021;Stover et al, 2017). Además, se debe tener en cuenta que la satisfacción de las NSB puede ser predictora positiva tanto de la motivación autónoma, como del autoconcepto físico del alumnado, aumentando la fidelización en la práctica (Valero-Valenzuela et al, 2021).…”
Section: Introductionunclassified
“…An evaluation was carried out of the tolerance index and the independence of the variables included in the regression equation. The tolerance index calculated was between .67 and .86 while the variance inflation factor (VIF) was between 1.01 and 1.45; these values rule out the probability of error derived from possible collinearity (Hair et al, 2018). Similarly, the values obtained for the Durbin-Watson statistic (between 1.67 and 1.92) confirm the independence of the data (Gil, 2003).…”
Section: Linear Regressionmentioning
confidence: 73%
“…For example, in a study looking at secondary school students, Estrada (2020) concluded that the higher the students' EI developmental levels, the higher their levels of resilience. Furthermore, both constructs are related to developing socio-emotional competencies (González-Fernández et al, 2022), so both capacities, along with the competencies associated with them, could be strengthened, and enhanced if they were worked on together in the educational field (Cejudo et al, 2016;Hernández-Andreo et al, 2021;Troy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature has shown the importance of students’ intrinsic satisfaction, development of emotional intelligence, their basic psychological needs in school, academic motivation, self-esteem, and even the physical activity they practice in their leisure time (PA-LT), having an impact on students’ learning process [ 3 , 4 , 5 , 6 , 7 ]. Despite the fact that the international literature is rather clear, there are just a few national researchers that analyze these factors in the Mexican adolescents’ learning process framework [ 8 ].…”
Section: Introductionmentioning
confidence: 99%